Samadinia longispina, a new genus and species of deep-sea spider crab from the western Pacific, and a new species of Rochinia A. Milne-Edwards, 1875, from Papua New Guinea (Crustacea: Brachyura: Majoidea: Epialtidae) - Ng, Peter K.l.; de Forges, Bertrand Richer (Zootaxa, 2013)
A new genus, Samadinia n. gen., and new species, Samadinia longispina n. sp., of deep-water epialtid spider crab is described from French Polynesia and New Caledonia. The new genus is superficially similar to Rochinia A. Milne-Edwards, 1875, but can be distinguished by having the dorsal surface of the carapace covered with small, rounded granules (versus with long spines or strong tubercles), well developed hepatic and lateral branchial spines (versus relatively shorter and weaker), a prominently constricted male thoracic sternite 4 (versus relatively broader with less prominent or without median constriction) and a proportionally broader male abdomen. A new species of Rochinia, R. granulosa n. sp., is also described from Papua New Guinea. It is easily distinguished from congeners its small adult size, the presence of numerous relatively large granules on the carapace and a relatively short hepatic spine.